The Influence of Crew Skills on the Use of Navigation Equipment and Its Impact on Shipping Safety: A case study at PT Al Jazeera Shipping Company - Permatasari, Citra; Noreng, Robertus (Diponegoro University, 2023)
Technological progress in transportation, especially sea transportation, is necessary for a maritime nation. It is essential for ensuring the distribution of goods and mobilizing passengers between islands. Additionally, it is crucial for the maintenance of these systems. Every individual who works in this sector must be able to adapt to and maintain the stability of technological machinery. Technological advances have led to rapid development in various fields, including the maritime sector. However, these advances can lead to fatal work accidents if not balanced with qualified skills. Work accidents in the maritime transportation industry caused by human error result in significant losses for both ship passengers and companies. This study focuses on the initial skills of PT AJS ship crews in using navigation equipment. The research results show that the skills of ship crews in using navigation equipment significantly influence the safety of the shipping fleet.